Implementation of Higher Diploma Training in Educators’ Instructional Process at three Colleges of Teachers Education of Oromia Region (Ethiopia) - Abayneh Lemma; Desta Gebeyehu; Kassa Michael; Mulugeta Atnafu; Tadesse Hagos (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
This study examines the extent to what the program implemented in educators' instructional process. A survey research method of mixed approach was employed by which observation, questionnaire and interview were used as data gathering tools. As a result, the overall extent to which the programme is being applied in the educators' instructional process was found to be not satisfactory due to session planning and action research that seen as not being practiced at all in the colleges. Besides, most limitations identified during observation overlap with that of our pre-service teachers diagnosed during independent teaching practice. As influential factors, three potential challenges were found and discussed in line with the desired recommendations.